Aspects of parenting and family functioning associated with obesity in adolescent refugees and migrants from African backgrounds living in Australia - David Mellor; Andre Renzaho; Boyd Swinburn; Julie Green; Ben Richardson (Elsevier, 2012)
Abstract Objective: To investigate the relationship between parenting style and family functioning, and BMI, among adolescent migrants and refugees from African countries. Method: A total of 104 parents and their adolescent offspring completed questionnaires assessing the variables of interest, and anthropometric data were collected from them. Results: Parents reported higher maternal involvement, lower levels of paternal involvement, higher levels of positive parenting, greater use of 'other' (non‐corporal) discipline styles, greater satisfaction and better communication than did their offspring. Parents also reported greater family cohesion and flexibility than adolescents, and saw their families as more enmeshed and more rigid. Parenting style and family functioning were not strong predictors of BMI according to either report. For adolescents, inconsistent discipline and lack of parental supervision accounted for significant variance in BMI. Conclusions: Inconsistent discipline and lack of parental supervision may be related to adolescent BMI. Further studies with larger samples are required to confirm these relationships with the view to informing obesity prevention programs for this target population. Implications: Prevention or intervention programs aimed at reducing the prevalence of overweight and obesity need to consider parenting style in their design.